Extracellular vesicle‐packaged mitochondrial disturbing miRNA exacerbates cardiac injury during acute myocardial infarction. Issue 4 (22nd April 2022) - Sun, Ping; Wang, Chao; Mang, Ge; Xu, Xiangli; Fu, Shuai; Chen, Jianfeng; Wang, Xiaoqi; Wang, Weiwei; Li, Hairu; Zhao, Peng; Li, Yifei; Chen, Qi; et al.
Abstract: Mounting evidence suggests that extracellular vesicles (EVs) are effective communicators in biological signalling in cardiac physiology and pathology. However, the role of EVs in cardiac injury, particularly in ischemic myocardial scenarios, has not been fully elucidated. Here, we report that acute myocardial infarction (AMI)‐induced EVs can impair cardiomyocyte survival and exacerbate cardiac injury. EV‐encapsulated miR‐503, which is enriched during the early phase of AMI, is a critical molecule that mediates myocardial injury. Functional studies revealed that miR‐503 promoted cardiomyocyte death by directly binding to peroxisome proliferator‐activated receptor gamma coactivator‐1β (PGC‐1β) and a mitochondrial deacetylase, sirtuin 3 (SIRT3), thereby triggering mitochondrial metabolic dysfunction and cardiomyocyte death. Mechanistically, we identified endothelial cells as the primary source of miR‐503 in EVs after AMI. Hypoxia induced rapid H3K4 methylation of the promoter of the methyltransferase‐like 3 gene ( METTL3 ) and resulted in its overexpression. METTL3 overexpression evokes N6‐methyladenosine (m 6 A)‐dependent miR‐503 biogenesis in endothelial cells. In summary, this study highlights a novel endogenous mechanism wherein EVs aggravate myocardial injury during the onset of AMI via endothelial cell‐secreted miR‐503 shuttling. Abstract : Extracellular vesicles serve as early master regulators to exacerbate myocardial injury in acute myocardial infarction (AMI). Exosomal miR‐503 is a critical molecule that triggers mitochondrial dysfunction and cardiomyocyte death via the PGC‐1β/NRF‐1 and SIRT3/PDH/ATP synthase communication axes. The initiation and biogenesis of miR‐503 are dependent on H3K4me3/METTL3‐mediated m 6 A modification of pri‐miR‐503 in cardiac endothelial cells during AMI.